Treatment of chronic kidney disease stage 3～4 with "WeChat+chronic disease management" model - Sheng Ling-li; Wang Lin; Zhang Xian-wen; Zhang Quan (Linchuang shenzangbing zazhi)
Objective To explore the efficacy of "WeChat+full-course chronic disease management" mode for chronic kidney disease（CKD）stage 3～4.Methods A retrospective study was performed for 72 hospitalized CKD patients from January 2018 to March 2019.They were divided into conventional and WeChat groups（n=36 each）according to the different health management models.The routine group received conventional management mode while WeChat group had "WeChat+full chronic disease management" mode.The follow-up period was 1 year.Two groups were compared with regards to estimated glomerular filtration rate（eGFR）,albumin,potassium,phosphorus,hemoglobin,24 h urinary protein quantification,post-intervention efficiency,quality-of-life,disease awareness,medication compliance,diet compliance and satisfaction.Results After interventions,blood and urine parameters of two groups significantly improved as compared with those pre-treatment（P<0.05）.Blood and urine parameters were significantly better in WeChat group than those in conventional group.The effective rate of WeChat group was significantly higher than that of conventional group（94.44% vs 77.78%）.And the difference was significant（P<0.05）.WeChat group was significantly higher than conventional group in terms of psychological disorders,living conditions and self-care capability（P<0.05）.The disease awareness rate,medication compliance rate and diet compliance rate were significantly higher in WeChat group than those in conventional group.And there were significant differences（P<0.05）.The satisfaction degree of model was significantly higher than that of conventional group（94.44% vs 80.56%）and the difference was significant（P<0.05）.Conclusions WeChat+full chronic disease management model is indicated for patients with varying degrees of disease.And early preventions may achieve better education outcomes,prevent kidney disease more effectively and delay the progression of kidney disease.